Answer:
y - 5 = -2(x + 3)
Step-by-step explanation:
When you write an equation in point-slope form, you only need two things: a point and a slope.
Given:
point: (-3, 5)
slope (m): -2
The standard point-slope equation is
y - y₁ = m(x - x₁)
Plug in what you know.
y - (5) = -2(x - (-3))
Simplify.
y - 5 = -2(x + 3)
This is your equation.
Learn with another example:
brainly.com/question/24436844
Blue was not the imposter.
To simplify <span>2x + 8 = -6, the easiest way is to manipulate the equation one step at a time:
</span>2x + 8 = <span>-6
</span>2x = <span>-14 (subtract 8 from both sides)
</span>x = -7 (divide both sides by 2)
Answer:
43.48
Step-by-step explanation:
Answer:
55.9548
Step-by-step explanation:
35.64 ÷ 2 = 17.82
17.82 × 3.14 = 55.9548